Chemical and structural characterization of ZrCNAg coatings: XPS, XRD and Raman spectroscopy - Velasco, Sebastian Calderon (2015)
In this report Zr C N Ag coatings produced by dual magnetron sputtering are characterized by X-ray photoelectron spectroscopy (XPS) and complemented byX-ray diffraction, scanning electron microscopy, electron-probe microanalysis and Raman spectroscopy, in order to determine the chemical bonds and phases formed during the production process. The results demonstrate the possibility of producing coatings with different silver content (0–16 at.%), in which zirconium carbonitrides (70–95 at.%), amorphous carbon nitride phases (0–16 at.%) and residual zirconium oxide phases (∼5 at.%) coexists with the metallic silver. The profile analysis evidenced a highly oxidized surface due to the affinity of Zr to form ZrO2, and silver segregation to the surface. The composition after Ar+ bombardment revealed the contribution of silver clusters and metallic silver, together with the mentioned phases that vary in content depending on the deposition parameters utilized. STEM images revealed silver nanoparticles distributed in the Zr C N matrix with sizes around 5–20 nm, as well as silver surface agglomeration with sizes <80 nm.